Local and Migrant Fishermen Marine Cultures in the Atapupu Coastal Area in Supporting the Blue Economy in Maritime Security - Muh. Afrisal; Raymundus Putra Situmorang; Kristera Tesa Bere Mau; Ari Widodo; Andik Isdianto; Intan Dwi Puspitasari; Supriyadi Supriyadi (The Republic of Indonesia Defense University, 2023)
Atapupu is a coastal area that has a strategic location because it is directly adjacent to the country of Timor Leste. This study aims to analyze the differences in marine culture at Atapupu Beach in supporting the blue economy in maritime security. This study uses a qualitative method with a descriptive approach. The data source comes from primary data by interviewing local and migrant fishermen and secondary data comes from journals. Data analysis in this study used descriptive qualitative. This study found that the differences between the local and migrant fishermen could be differentiated based on their time to go to sea, the fishing gear, and the type of boat used by the fishermen. The migrant fishermen, which come from Buton, are Muslim, so they do not go to sea on Fridays due to Fridays Prayers. They use fishing rods as gear and bigger boats than the local fishermen. Meanwhile, the local fishermen have no special days to go to sea, they go to sea depending on the weather conditions. The local fishermen only use nets as fishing gear and their boats are smaller compared to the migrant fishermen’s boats. These conditions are affecting their range of fishing areas, the type of fish caught, and the average income per month. Cultural differences at sea between local and migrant fishermen will certainly affect maritime security in the blue economy sector. The existence of differences in types and income from catches can lead to less optimal utilization of fishery resources.